Makanan Halal dan Tayyib dalam Perspektif Al-Quran - Sri Mulyati; Achmad Abubakar; Hasyim Hadade (Jurnal Ilmu Sosial dan Humaniora, 2023)
With the increasing trend of demand for halal food, various food products have emerged with many variations to compete in the market, to meet the practical needs of consumers and not to forget the delicacy in food. This is the background for producers in developing their products, so it is not uncommon for some producers to feel the need to add dyes to attract consumers' attention, preservatives, flavorings and even artificial sweeteners, all of which come from chemicals which are considered quite cheap and easy to obtain on the market. Seeing this phenomenon, with the emergence of many "halal" and "instant" foods that continue to develop along with human needs, which directly or indirectly have an impact on the human body, the author feels the need to examine more deeply regarding the meaning of the verse halalan ṯayyiban which can be applied in everyday life. This research paper is included in the category of library research using literature, including the Al-Quran and its commentaries as primary sources and other supporting scientific articles as secondary sources. Halal food is food that is acceptable for consumption and does not result in torment (sin). Meanwhile, the meaning of ṯayyib is good, holy, nutritious, proportionate and safe. The implication for the selection of food products is that it is better to pay attention to three aspects of the meaning of ṯayyib, namely choosing food that is healthy (beneficial for the body/nutritious), proportional (not consuming excessively), safe (not toxic/expired).